1998
DOI: 10.1002/(sici)1097-0169(1998)40:4<354::aid-cm4>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thiol protease inhibitors on myoblast fusion and myofibril assembly in vitro

Abstract: To investigate the roles of thiol proteases such as cathepsins and calpains in muscle differentiation, we have treated primary cultures of pectoralis muscle with a variety of protease inhibitors and examined the effects these agents have on myoblast fusion and myofibrillogenesis. We have found that a membrane‐permeable inhibitor, E64D, has dramatic effects on both events of muscle differentiation. Cells treated with this inhibitor display gross morphological changes, severe delays in myofibril assembly, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Second, acid‐activatable pro‐catB is secreted from differentiating myoblasts in culture [Jane and Dufresne, 1994]. Third, exposure of differentiating myoblasts to the cell‐penetrating catB selective inhibitor, CA074Me inhibits myotube formation, while exposure of primary myoblasts to the cell‐penetrating cysteine protease general inhibitor, E‐64d, negatively affects myotube formation and is associated with a build‐up of β1‐Integrin [Moncman and Wong, 1999]. Fourth, catB gene‐trapped myoblasts transfected with sense preprocatB cDNA form myotubes similar to those formed in control myoblasts, while control myoblasts transfected with antisense constructs form myotubes similar to those formed in catB gene‐trapped myoblasts [Gogos et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…Second, acid‐activatable pro‐catB is secreted from differentiating myoblasts in culture [Jane and Dufresne, 1994]. Third, exposure of differentiating myoblasts to the cell‐penetrating catB selective inhibitor, CA074Me inhibits myotube formation, while exposure of primary myoblasts to the cell‐penetrating cysteine protease general inhibitor, E‐64d, negatively affects myotube formation and is associated with a build‐up of β1‐Integrin [Moncman and Wong, 1999]. Fourth, catB gene‐trapped myoblasts transfected with sense preprocatB cDNA form myotubes similar to those formed in control myoblasts, while control myoblasts transfected with antisense constructs form myotubes similar to those formed in catB gene‐trapped myoblasts [Gogos et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…271 Pectoralis muscle cells and myoblasts treated with E-64d display morphological changes, delays in myofibril assembly, and reduced ability to fuse to form multinucleated myotubes. 272,273 Recently, it was shown that E-64d prevents both calpain up-regulation and apoptosis in the lesion and penumbra following spinal cord injury in rats. 274,275 E-64d has been associated with attenuation of parathyroid hormone in osteoblasts, 276,277 prevention of calcium ionophore cataracts, 278 antiviral activity on foot-and-mouth-disease virus, 279 inhibition of coronavirus protein processing, 280 and many other biological and physiological processes.…”
Section: Table 25 Inactivation Of Cysteine Proteases By Epoxysuccinyl...mentioning
confidence: 99%
“…These genes encode proteins that mediate key processes of recognition and adhesion and formation of a prefusion complex, as well as plaque, cell alignment and plasma membrane apposition and plasma membrane breakdown, respectively. Molecules that have been implicated in mammalian skeletal muscle differentiation include active protease nexin, Ca 2+ , cathespin B, desmin, GRP49, ERK6, m-calpain, NCAM, N-cadherin, proteasomes and the H145 antigen (Crescenzi et al, 1994;Dourdin et al, 1999;Dourdin et al, 1997;Gogos et al, 1996;Gorza and Vitadello, 2000;Hyodo and Kim, 1994;Lechner et al, 1996;Li et al, 1994;Moncman and Wang, 1998;Peck and Walsh, 1993;Seigneurin-Venin et al, 1996). Extending our knowledge of intercellular interactions in vertebrate muscle development may aid in the understanding of muscle tissue repair, which includes the reassembling of intercalated disks in the infarcted or hibernating heart (Kaprielian et al, 1998;Matsushita et al, 1999), and the fusion of satellite cells with damaged myotubes in skeletal muscle after exercise (Anderson, 1998).…”
Section: Introductionmentioning
confidence: 99%